Matrix Metalloproteinases in COPD and atherosclerosis with emphasis on the effects of smoking - Kraen, Morten (Lund University, 2019)
Matrix metalloproteinases (MMP´s) are known biomarkers of atherosclerosis. MMP´s are also involved in the pathophysiological processes underlying chronic obstructive pulmonary disease (COPD). Cigarette smoking plays an important role in both disease states and is also known to affect the concentration and activity of MMP´s systemically. Unfortunately, the epidemiological data concerning the value of MMP´s as biomarkers of COPD and atherosclerosis with special regards to smoking habits are limited. Methods: 417 subjects with records of smoking habits and tobacco consumption were examined with comprehensive spirometry, carotid ultrasound examination and biomarker analysis of MMP-1, -3, -7, -10 and -12

Mätning av blodnivå av Matrix Metalloproteinases vid kronisk obstruktiv lungsjukdom och åderförkalkning och rökning.
Matrix Metalloproteinases vid kronisk obstruktiv lungsjukdom och åderförkalkning
Keywords: Atherosclerosis; Ateroskleros; Pulmonary Disease, Chronic Obstructive; Kroniskt obstruktiv lungsjukdom; Matrix Metalloproteinase 3; Matrixmetalloproteinas 3; Matrix Metalloproteinase 1; Matrixmetalloproteinas 1; Matrix Metalloproteinase 7; Matrixmetalloproteinas 7; Matrix Metalloproteinase 10; Matrixmetalloproteinas 10; Matrix Metalloproteinase 12; Matrixmetalloproteinas 12; Clinical Medicine; Klinisk medicin